Character Association and Path Coefficient Analysis in African Marigold (Tagetes erecta L.) - Sahu, Jitendra Kumar; Sharma, Gaurav; Nair, S. K.; Netam, Neelima (International Journal of Bio-resource and Stress Management, 2018)
The present investigation entitled was conducted at the Horticultural Research cum Instructional Farm, Department of Floriculture and Landscape Architecture , Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.) during the year 2015 to study the performance of seventeen African marigold genotypes in Randomized Block Design replicated three times. Considerable variability for most of the characters was indicated by analysis of variance. Association among different characters was estimated at genotypic (G) and phenotypic (P) levels among 13 characters. Number of flowers plant-1 exerted highly significant positive correlation with fresh flower weight plant-1 (yield plant-1), dry flower weight plant-1, flower yield hectare-1 and xanthophyll content at genotypic and phenotypic level and significantly positive association with flower diameter at genotypic level only. The path-coefficient analysis revealed that, at genotypic level, fresh flower weight plant-1 expressed highest positive direct effect on number of flowers plant-1 followed by xanthophyll content, plant height, plant spread and secondary branches. Although yield hectare-1 shows highly significant positive correlation with number of flowers plant-1. At phenotypic level, fresh flower weight plant-1 showed high positive direct effect on number of flowers plant-1 followed by plant spread, number of secondary branches plant-1 and days to 50% flowering.